The impact of interaction quality of user-generated content on consumers' purchase intention - Katria Arintya Anindyantari; Sri Rahayu Hijrah Hati (President University, 2022)
Online social interaction has been around for a long time but has accelerated recently due to the aggressiveness of technology and digital penetration. Looking at the current conditions, it is undeniable that digitalization is one of the factors. For a company to grow, marketers must have a good interaction digitally with consumers. Online social interaction changes rapidly and constantly include user-generated content and peer-to-peer exchanges. Per social cognitive theory, it can be concluded that user-generated content's interaction quality will affect consumers' purchase intentions. This study examined the effects of interaction quality of user-generated content on online shopping intention. Following the theoretical basis of the Technology Acceptance Model (TAM) combined with the Extended Technology Acceptance Model (ETAM), the researcher used the original construct of perceived usefulness, two constructs related to perceived trust and perceived credibility, to understand better the effect of promotional content and its impact on purchase intention 250 respondents participated in this research, data was gathered from a survey administered to online shopping consumers and a partial least square analysis was used to test the research model. This study's findings help marketers evaluate performance based on consumer behavior towards user-generated content.